Evaluation of growth performance in cyclically mated populations of Malaysian giant prawn, Macrobrachium rosenbergii, in Malaysia - Elsheikh, Mohamed Omer; Mohd Fariduddin Othman,; Faruq, Golam; Eid, Ihlam Ibrahim; Subha Bhassu, (Universiti Kebangsaan Malaysia, 2015)
Malaysian giant prawn, Macrobrachium rosenbergii (de Man, 1879), is an important crustacean aquaculture candidate globally cultured chiefly in hot climates and seasonally in temperate zones. Although the first hatchery for artificial production of the species was established in Malaysia in 1984, however, its genetic improvement program has just started recently. This study was executed as a part of this improvement project to evaluate morphometric growth related traits of four populations collected from the Western Coast of Peninsular Malaysia and their progenies. The results of the study disclosed significant differences among these populations for all traits that were considered; with Kedah population showing significant (p<.05) superiority over the rest. Within the eight successfully cohort progeny families produced, Kedah progeny group was the heaviest at the same level of significance as that of parental groups. Fixed effects of family, sex and their interactions showed high significance (p<.0001). Estimated heritability values for the traits mentioned above were moderate to high; i.e. 0.5788±0.2989, 0.5156±0.2753, 0.4277±0.2407 and 0.5120±0.2739 for weight, total length, tail length and carapace length, respectively. All mentioned results encourage us to un-hesitantly recommend selection for these traits in future genetic improvement of this species.